Incidence of downy mildew Plasmopara viticola (Berk. et Curtis ex. de Bary) Berl. et de Toni in Terceira island, Azores - Zorman, Matej (2018)
Downy mildew is one of the most economically important disease affecting vine production in Terceira island, Azores. By its incidence, frequency and quantity of pathogens, supported with favourable temperate humid climate conditions, this disease is difficult to control in terms of sustainable integrated plant protection policy. The objectives of INTERFRUTA project were to determine the incidence of the disease, to better understand it and to adopt an adequate forecasting model with necessary adjustments to predict the disease appearance and its in-time integrated plant protection control measures. Plasmopara viticola was directly observed in two weeks time periods on seven representative vineyards at different altitudes. Three of the monitored plots were established during study inside one plantation. Incidence was registered as result of visual symptoms in percentage, where 10% of plants in each vineyard were observed. Seasonal evolution of the disease was studied in one of the wine producing area.